Identifying urban design principles and its attributes for waterfront transit-oriented development (WTOD) - Redzuan, Nabilah; Abdul Latip, Nurul Syala; Ismail, Noorhayati; Ujang, Norsidah (Malaysia Institute of Planners, 2022)
The booming development of transit-oriented development (TOD) worldwide, especially in high-density urban areas, has shown that many cities have started to transform their urban spaces into more sustainable and liveable cities. TOD integrates the mixed-use development around the public transport stations and promotes a pedestrian-and bicycle-friendly environment as a city lifestyle. However, such developments often lack integration with the contextual condition of the surrounding area, which in the case examined in this study is the waterfront. Many cities in developed countries such as Singapore, U.S. and Canada have started to reintegrate their TODs with the water bodies. Recent trends show that TODs are widely established in areas near the water body such as dockland and waterfront, as part of urban regeneration. Various urban design principles of waterfront transit-oriented development are available, but most of them are scattered across many documents. Thus, this research aimed to identify the urban design principles for waterfront transit-oriented development. The principles were developed using a qualitative method that included content analysis of journals, reports, and guidelines on transit-oriented development (TOD), waterfront development, and waterfront transit-oriented development (WTOD). In the end, the urban design principles of WTOD can guide professional stakeholders such as architects, planners, engineers, and others relevant to the field to reintegrate the TOD with the waterfront in future planning.